To simplify the expression 5(7x - 2) - 14x + 4, you can distribute the 5 to the terms inside the parentheses:
5(7x - 2) - 14x + 4 = 35x - 10 - 14x + 4
Next, combine like terms:
35x - 10 - 14x + 4 = (35x - 14x) + (-10 + 4) = 21x - 6
Therefore, the simplified expression is 21x - 6.
simplify 5( 7x - 2) - 14x + 4
7 answers
17d - 33 + 9 (2d + 6) - 11
To simplify the expression 17d - 33 + 9 (2d + 6) - 11, we must start by distributing the 9 to the terms inside the parentheses:
9(2d + 6) = 18d + 54
Rewriting the expression with the distribution gives us:
17d - 33 + 18d + 54 - 11
Next, combine like terms:
(17d + 18d) + (-33 + 54 - 11) = 35d + 10
Therefore, the simplified expression is 35d + 10.
9(2d + 6) = 18d + 54
Rewriting the expression with the distribution gives us:
17d - 33 + 18d + 54 - 11
Next, combine like terms:
(17d + 18d) + (-33 + 54 - 11) = 35d + 10
Therefore, the simplified expression is 35d + 10.
6(3q - 4)+ 18 - 12q - 7(4q+5)
To simplify the expression 6(3q - 4) + 18 - 12q - 7(4q + 5), let's begin by distributing the 6 and the -7:
6(3q - 4) + 18 - 12q - 7(4q + 5) = 18q - 24 + 18 - 12q - 28q - 35
Next, combine like terms:
(18q - 12q - 28q) + (-24 + 18 - 35) = -22q - 41
Therefore, the simplified expression is -22q - 41.
6(3q - 4) + 18 - 12q - 7(4q + 5) = 18q - 24 + 18 - 12q - 28q - 35
Next, combine like terms:
(18q - 12q - 28q) + (-24 + 18 - 35) = -22q - 41
Therefore, the simplified expression is -22q - 41.
-5+ 3/4 (8h + 12) - 10h
To simplify the expression -5 + 3/4 (8h + 12) - 10h, let's begin by distributing the 3/4:
3/4 (8h + 12) = (3/4)(8h) + (3/4)(12) = 6h + 9
Rewriting the expression with the distribution gives us:
-5 + 6h + 9 - 10h
Next, combine like terms:
(6h - 10h) + (-5 + 9) = -4h + 4
Therefore, the simplified expression is -4h + 4.
3/4 (8h + 12) = (3/4)(8h) + (3/4)(12) = 6h + 9
Rewriting the expression with the distribution gives us:
-5 + 6h + 9 - 10h
Next, combine like terms:
(6h - 10h) + (-5 + 9) = -4h + 4
Therefore, the simplified expression is -4h + 4.